2020
DOI: 10.3390/en13092248
|View full text |Cite
|
Sign up to set email alerts
|

Study of How Photoelectrodes Modified by TiO2/Ag Nanofibers in Various Structures Enhance the Efficiency of Dye-Sensitized Solar Cells under Low Illumination

Abstract: Dye-sensitized solar cells (DSSCs) are low-cost solar cells belonging to the thin-film photovoltaic cell type. In this study, we studied the photovoltaic performances of DSSCs based on titanium dioxide (TiO2) nanofibers (NFs) containing silver (Ag) nanoparticles (NPs) under low illumination. We used the sol-gel method with the electrospinning technique to prepare the TiO2 NFs containing Ag NPs. Herein, we used two ways to add TiO2/Ag NFs to modify the photoelectrode successfully and enhance the performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The anode material in DSSC should provide a high surface area in order to host a large number of photoactive dye molecules [174]. However, by increasing the surface area of TiO 2, the number of surface states increases, leading to higher rates of recombination [175]. Moreover, the heat treatment of TiO 2 at temperatures around 450 • C to form the anatase phase which is favorable for DSSC, leads to the formation of oxygen vacancies [176].…”
Section: Solar Cellmentioning
confidence: 99%
“…The anode material in DSSC should provide a high surface area in order to host a large number of photoactive dye molecules [174]. However, by increasing the surface area of TiO 2, the number of surface states increases, leading to higher rates of recombination [175]. Moreover, the heat treatment of TiO 2 at temperatures around 450 • C to form the anatase phase which is favorable for DSSC, leads to the formation of oxygen vacancies [176].…”
Section: Solar Cellmentioning
confidence: 99%
“…Toward enhance light harvesting and reduce recombination loss, photoanode mesoporous layers have to be improved in term of thickness and light scattering ability. To accomplish this, Nien et al, 118 synthesized TiO 2 nano‐fibers containing silver (Ag) NPs (TNSN) by the sol–gel process for use as a photoanode in DSSC. Both TNSN and pristine TiO 2 were used in the preparation: first, TNSN was mixed with pristine TiO 2 and then the TiO 2 layer was covered with TNSN.…”
Section: Various Strategies To Improving the Efficiency Of Dsscsmentioning
confidence: 99%
“…According to Huang et al [29], the incident light power was too low under the illumination of 10 mW/cm 2 so that the electrons were intercepted by the oxidized electrolyte. Nien et al [30] showed that under low illumination, DSSCs can reduce the recombination reaction to enhance PCE, and the LSPR effect of AgNPs made more effective use of visible light radiation. In our work, under the low illumination of 10mW/cm 2 , the Schottky barrier interacting with AgNWs and TiO2 inhibited the recombination of charge and electrolyte, and the PCE increased to 8.78%.…”
Section: τN = R2 × C2mentioning
confidence: 99%